Gut Microbiota Dysbiosis Drives Resistance Gene Transfer and Bacterial Adaptation: Review - Ali, Shaymaa Mahmood; Tuama, Ammar Adnan (Universitas Muhammadiyah Sidoarjo, 2025)
Antimicrobial resistance (AMR) has emerged as a global health crisis, threatening the efficacy of modern medicine. The gut microbiota, a densely populated microbial ecosystem, plays a critical role in modulating host immunity, metabolism, and resistance to pathogen colonization. Disruption of this microbial balance—gut dysbiosis—creates an environment conducive to the proliferation and horizontal transfer of antibiotic resistance genes (ARGs), contributing to the development of multidrug-resistant organisms (MDROs). This review explores the molecular and ecological mechanisms through which gut dysbiosis influences AMR and examines therapeutic approaches aimed at restoring microbial homeostasis to combat this pressing challenge. Antimicrobial resistance (AMR) is a pressing global health concern, and recent studies have revealed the human gut microbiota as a significant reservoir of resistance genes. Dysbiosis—an imbalance in the composition and function of gut microbiota—can enhance the persistence and transfer of antibiotic resistance genes (ARGs) among microbial populations. This review explores the mechanisms linking gut dysbiosis to AMR, highlights recent findings on microbial-host interactions, and discusses emerging therapeutic strategies such as probiotics, fecal microbiota transplantation (FMT), and microbiota-modulating diets to combat resistance development. Understanding these dynamics is critical for advancing personalized medicine and curbing the spread of drug-resistant infections. Highlights: Dysbiosis Promotes AMR – Gut imbalance helps antibiotic resistance genes spread. Gut as ARG Reservoir – The gut hosts many resistance genes that can transfer between microbes. Therapies Target Microbiota – Probiotics, FMT, and diets may restore balance and fight AMR. Keywords: Gut Microbiota, Antimicrobial Resistance, Dysbiosis, Probiotics, Therapeutic Strategies